Perceptions of demotion decisions: A social capital perspective - Hennekam, S.; McKenna, Stephen; Richardson, Julia; Ananthram, Subra (ELSEVIER SCI LTD, 2019)
© 2019 Elsevier Ltd This article examines how demotees and co-workers understand involuntary demotion decisions, using a social capital lens. Drawing on data based on semi-structured in-depth interviews from 23 demotees and 46 co-workers (two co-workers of each demoted worker), we find that the likelihood of being demoted is determined by several factors. The personal characteristics of the demotee influence three aspects of social capital: 1) the quality of the employee-management relationship, 2) the ability to socialise with other organizational members and 3) visibility in the organization. Our findings contribute to the relational embeddedness perspective of social capital as well the growing body of literature on the dark side of social capital in organizations by showing how a lack of social capital impacts on demotion decisions. Relevant implications for organizations and HR practitioners for utilizing demotion as a HR tool are discussed.